Indicadores de actividad cultural y potencial creativo en Portugal: estudio regional para NUT 3 - Figueira, Jorge (2018)
The creative economy has been the subject of increasing interest in recent years, both in the area of cultural economics as well as in economic development studies and the analysis of spatial disparities. The underlying notion is to consider creative capital as a production factor linked to talent, technological innovation and initiative, which may shape part of an area or region’s economic flows, replacing merely physical production factors. Clearly, many of the activities to emerge from creative capital are based mainly on culture and cultural activities. Yet, their ultimate goal is not to produce purely artistic artefacts aside from the market but to create marketable prototypes which are differentiated due to their design and innovative nature. This is why, today, creative activities might have a greater impact on economic development than talent, perceived in the conventional sense. Based on these considerations, the current work seeks to explore the territorial distribution of cultural activities and creativity in Portugal and to ascertain the relationship with the level of economic development. This involves defining the cultural and creative sector and its main components, for which purpose we follow the definition of cultural sector from Maheus (2010) and we draw on R. Florida’s (2002) widely embraced factors; talent, technology, and tolerance. The level of territorial disaggregation is NUTS 3. The technique applied is based on multivariate statistical analysis, essentially, factorial analysis to construct synthetic indicators for creativity and development; and cluster analysis to determine homogeneous areas in the resulting distribution. We build partial indicators from the main conceptual branches of the cultural sector and creativity and we also estimate a new global synthetic indicator based on the main components obtained before by factorial analysis. As expected, the most salient preliminary findings to emerge from the study point to a concentration of creative activities mainly in the areas around Lisbon and Oporto, there also being agglomeration factors around university cities and other places which